EFFECT OF MATERNAL FOLIC ACID/IRON INTAKEON THE WEIGHT OF NEWBORNS IN OBSTETRIC WARD OFTERTIARY CARE HOSPITALS OF PUNJAB - Tahira Raza (Baqai Journal of Health Sciences)
A cross-sectional study has been designed to determine the influence of maternal folic acid and iron intake during pregnancy on newborns birth weight. The study was conducted from April–May 2014 at CMH Lahore Medical College and Institute of Dentistry, Services Hospital, Sir Ganga Ram, Lady Willingdon, Akhtar Saeed Trust and Mansoorah Hospitals in Lahore while Nishtar Hospital in Multan and Amina Hospital in Sialkot. About 300 females from the hospitals were selected by convenience sampling technique. A verbal consent was obtained before collecting data and the questionnaires were filled by the students. Majority of the 300 females (68.1%) who have been questioned during the study were between 22–30 years of age (selected range was 17–44 years) while the mean age was 28.5 years. Of the total studied population, 72% of the females took folic acid, 79.7% took iron and other multivitamins and 87% consumed leafy vegetables as a part of the routine diet. It was also noted that the average age at first pregnancy was between 20–24 years for 49% of the studied females. However, a gap of two years between successive pregnancies was found in only 33.3% cases. On the other hand, only 19.7% were graduates while 21.3% were illiterate. The study also included the correlation of household income with folic acid and iron intake. About 53.3% of the females with an income of 16,000 PKR or higher, reported better intake (folic acid 81.8%; iron 87.5%) than those with income of 15000 PKR or lower (46.7%) (folic acid ~61%; iron ~71